Nanofur for Biomimetic Applications. Issue 4 (28th March 2014) - Röhrig, Michael; Mail, Matthias; Schneider, Marc; Louvin, Henri; Hopf, Andreas; Schimmel, Thomas; Worgull, Matthias; Hölscher, Hendrik
<x xml:space="preserve">Abstract</x> Many plants and insects possess multi‐functional surfaces covered by dense nanohair. Such a nanofur is of high interest for various biomimetic applications like self‐healing, air retention, and oil/water separation. Here, we introduce a highly scalable and competitive molding technique for the fabrication of biomimetic nanofur. With this method, we pull nanofur out of flat polycarbonate and tune its wettability from hydrophilic to superhydrophobic. By mechanically structuring these samples we create various devices suitable for microfluidics. The nanofur can be also used for the fabrication of self‐healing surfaces inspired by pitcher plants as well as for air‐retaining surfaces mimicking the water fern Salvinia minima. Finally, we utilize the nanofur for oil/water separation and the cleaning of oil spills.